Reaching the missing millions through public-private mix (PPM) for TB prevention and care - Dias, Hannah Monica (Henry Stewart Talks, 2022)
Public-private mix (PPM), The impact of Covid-19 on the access to services, PPM can reduce the burden of drug-resistant TB, Global provision of TB preventative treatment, Opportunities for action, Monitoring, evaluation, and accountability in PPM, Private health care providers in TB care and prevention, PPM roadmap